Proceedings of the International Conference and the 10th Congress of the Entomological Society of Indonesia (ICCESI 2019) 2020
DOI: 10.2991/absr.k.200513.005
|View full text |Cite
|
Sign up to set email alerts
|

Mealybugs (Hemiptera: Pseudococcidae) Associated with Dragon Fruit in Indonesia

Abstract: Mealybugs were recorded on dragon fruit, Hylocereus undatus (Family: Cactaceae) in Indonesia. The present of certain mealybug species on dragon fruit has become quarantine concern in country where the mealybugs species is absent. The objective of this study was to identify mealybugs species associated with dragon fruit and record the live specimen of adult females mealybug. Mealybugs were collected from 3 locations: Bogor (West Java), Banyuwangi (East Java), and Pontianak (West Kalimantan). Mealybugs found in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Damage symptoms caused by these pests are a dry skin surface, fruit shrinkage, wrinkled skin, and honeydew which causes sooty molds (Mani and Shivaraju 2014;Nurhafizhah et al 2020). According to Sartiami et al (2019), the mealybug species found on dragon fruits in Indonesia are Ferrisia virgata (Cockerell), Phenacoccus solenopsis Tinsley, Planococcus minor (Maskell), and Pseudococcus jackbeardsleyi Gimpel & Miller, which belong to the family Pseudococcidae, order Hemiptera. In addition to dragon fruit, all these four mealybug species have a wide range of host plants.…”
Section: Introductionmentioning
confidence: 99%
“…Damage symptoms caused by these pests are a dry skin surface, fruit shrinkage, wrinkled skin, and honeydew which causes sooty molds (Mani and Shivaraju 2014;Nurhafizhah et al 2020). According to Sartiami et al (2019), the mealybug species found on dragon fruits in Indonesia are Ferrisia virgata (Cockerell), Phenacoccus solenopsis Tinsley, Planococcus minor (Maskell), and Pseudococcus jackbeardsleyi Gimpel & Miller, which belong to the family Pseudococcidae, order Hemiptera. In addition to dragon fruit, all these four mealybug species have a wide range of host plants.…”
Section: Introductionmentioning
confidence: 99%
“…M ealybugs (Hemiptera: Coccoidea: Pseudococcidae) are globally distributed, highly aggressive pests of many commercial, non-commercial, and ornamental plants [1][2][3] . They are a diverse group of sap-sucking insects, with at least 32 genera and around 105 species 4 .…”
mentioning
confidence: 99%